Mechanism of the selective sulfide oxidation promoted by HNO 3/FeBr3 - Kinen, Claudio Omar (2009)
The oxidation of aryl methyl sulfides containing electron withdrawing and electron donating groups (p-NO2, p-CHO, p-NCS, p-Br, H, p-CH3, p-OCH3) was carried out in homogeneous solution in acetonitrile in the presence of catalytic amounts of HNO3 and FeBr3. The FeBr3 is required for the reaction to proceed for compounds with strongly electron withdrawing groups (p-NO2 and p-CHO) but is not necessary in the case of all the other compounds, although in the latter cases the yield decreases considerably. The rate of the reaction was measured as a function of substrate, FeBr3 and HNO3 concentration. From the experimental data a mechanism is suggested where there are two reaction pathways, one involving the formation of a ternary complex between the substrate, FeBr3 and NO 3- and one involving a complex formed between the sulfide and the HNO3. From these complexes HNO2 is generated, which then combines with HNO3 to yield N2O4, initiating a catalytic cycle where the sulfide is oxidized and O2 from the air is stoichiometrically consumed.